1995
DOI: 10.1007/bf01553519
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament patellar tendon reconstruction: it is probably better to leave the tendon defect open!

Abstract: The purpose of our prospective study was to establish whether or not in anterior cruciate ligament (ACL) patellar tendon reconstruction the tendon defect has to be closed. In 50 consecutive ACL patellar tendon reconstructions, the tendon defect was randomly closed (group I) or left open (group II). The following data were recorded from all patients on the 4th and 14th days post operation: range of motion (ROM), pain at rest, pain and validity at isometric contraction, ability of bent leg raising (at 4th day) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Aggressive versus non-aggressive rehabilitation protocol In our experimental model, the scar tissue was present only in the central-third of the tendon (donor site defect), and not in the medial and lateral thirds (remaining tendon). This finding is in agreement with that reported by other authors [7]. Cerullo et al [7], using CT and ultrasonography, compared extension of the scar tissue in two different situations: (1) the PTDD was left open (25 cases) and (2) the gap was closed reapproximating the medial and lateral remaining patellar tendon (25 cases).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Aggressive versus non-aggressive rehabilitation protocol In our experimental model, the scar tissue was present only in the central-third of the tendon (donor site defect), and not in the medial and lateral thirds (remaining tendon). This finding is in agreement with that reported by other authors [7]. Cerullo et al [7], using CT and ultrasonography, compared extension of the scar tissue in two different situations: (1) the PTDD was left open (25 cases) and (2) the gap was closed reapproximating the medial and lateral remaining patellar tendon (25 cases).…”
Section: Discussionsupporting
confidence: 82%
“…Only a few studies have investigated the healing of the PTDD in humans [1,3,7,8,18,20,22,23] as well as in animals [6,11,14,19], and they have been primarily focused on the use of ultrasonography, CT, MRI, and biomechanical testing, rather than on histology. Moreover, little is known about the histologic healing pattern in the PTDD following PTA harvest, above all in the initial stages of the healing process; likewise, the source of recellularization of the defect has not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, painful bone spurs developed at the apex of the patella in some of their patients. In another study, Cerullo et al [9] found that if the patellar tendon was sutured, a scar process involving the entire patellar tendon and not only the central defect developed. In the present study, the remaining parts of the patellar tendon showed signs of a hypertrophic response to the poor healing of the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in the PT are not completely healed for months. [54][55][56] Lessening the severity of these complications by enhancing healing of the PT should lead to improved patient outcome. [57][58][59][60] The MCL, on the other hand, can heal but with a significantly different biochemical composition and matrix organization, resulting in inferior biomechanical properties even 2 years after injury.…”
Section: Functional Tissue Engineering Of Ligaments and Tendonsmentioning
confidence: 99%